Angiotensin-converting enzyme insertion/deletion gene polymorphism and interferon-β treatment response in multiple sclerosis patients: a preliminary report - Ristić, Smiljana; Starčević Čizmarević, Nada; Lavtar, Polona; Lovrečić, Luca; Perković, Olivio; Sepčić, Juraj; Šega Jazbec, Saša; Kapović, Miljenko; Peterlin, Borut (Pharmacogenetics and genomics, 2017)
We investigated the effect of the functional insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme (ACE) gene on the response to interferon-β (IFN-β) therapy in Croatian and Slovenian patients with multiple sclerosis (MS). A total of 275 IFN-β treated MS patients [162 responders (Rs) and 113 nonresponders (NRs)] were genotyped by PCR. The ACE I/D genotype distribution and allele frequencies did not differ between female Rs and NRs. However, male NRs tended to have a greater prevalence of the DD genotype (P=0.073; odds ratio: 2.64; 95% confidence interval: 0.91-7.60) and a significantly higher frequency of the D allele (P=0.022; odds ratio: 2.43; 95% confidence interval: 1.13-5.20) than male Rs. Multiple forward stepwise regression analysis indicated that the negative response to IFN-β therapy was associated with the ACE-DD genotype in men (β=0.371; multiple R change: 0.132; P=0.009) and a higher pretreatment relapse rate in both men (β=-0.438; multiple R change: 0.135; P=0.015) and women (β=-0.208; multiple R change: 0.042; P=0.034). The ACE I/D polymorphism and pretreatment relapse rate accounted for ∼26.7% of the IFN-β response variability among the men in the sample. Further studies of a larger number of MS patients from different populations are necessary to evaluate these preliminary findings.